Superfast 3D shape measurement of a flapping flight process with motion based segmentation - Li, Beiwen (SPIE, 2018)
Flapping flight has drawn interests from different fields including biology, aerodynamics and robotics. For such research, the digital fringe projection technology using defocused binary image projection has superfast (e.g. several kHz) measurement capabilities with digital-micromirror-device, yet its measurement quality is still subject to the motion of flapping flight. This research proposes a novel computational framework for dynamic 3D shape measurement of a flapping flight process. The fast and slow motion parts are separately reconstructed with Fourier transform and phase shifting. Experiments demonstrate its success by measuring a flapping wing robot (image acquisition rate: 5000 Hz; flapping speed: 25 cycles/second).